Analysis of Bama Gravel as Coarse Aggregate in Concrete Production: A Review - Muazu, N.; Muazu, H. I.; Isa, A. S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2026)
Bama gravel, a naturally occurring riverbed aggregate in Borno, Northeastern Nigeria, is widely used in concrete production due to its abundance and low cost. This naturally occurring aggregate from Bama ridge, extends over a distance of approximately 300 km. In the past few years, attention has been shifted by researchers to exploring the engineering potential of the aggregate. The review adopted systematic approach by collecting and analyzing studies on Bama gravel between 1999 and 2025. A total of 10 documents were identified, of which seven met the inclusion criteria and were analyzed to identify performance trends and research gaps. The review shows that more than 90% of the studies carried out on the aggregate are by indigenous researchers. This is due to the prior knowledge of these researchers on how the material is being patronized by local communities in the catchment area. The review also shows that existing studies are focused on grading of the aggregate, mix ratio optimization and partial replacement of cement or aggregates, demonstrating its suitability for producing medium and high strength concrete. However, key research gaps remain, as lack of established probabilistic properties of Bama gravel which are vital for reliability-based design. This limits its global applicability in the design of concrete. Its mineralogical composition is also undocumented, despite its potential impact on reactivity, strength, and durability. Long-term performance under diverse environmental conditions remains unstudied. Furthermore, the microstructural behavior within the cement matrix, including the interfacial transition zone and bonding characteristics, is unexplored. To our knowledge there never been any study that assessed its resistance to Sulphate attack, a critical factor for exposure to aggressive environments. Addressing these gaps will advance the understanding and global acceptance of Bama gravel as a durable and reliable aggregate for concrete production.